1997
DOI: 10.1073/pnas.94.25.13885
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering of cartilage in space

Abstract: Tissue engineering of cartilage, i.e., the in vitro cultivation of cartilage cells on synthetic polymer scaffolds, was studied on the Mir Space Station and on Earth. Specifically, three-dimensional cell-polymer constructs consisting of bovine articular chondrocytes and polyglycolic acid scaffolds were grown in rotating bioreactors, first for 3 months on Earth and then for an additional 4 months on either Mir (10 ؊4 -10 ؊6 g) or Earth (1 g). This mission provided a unique opportunity to study the feasibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
246
1
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 382 publications
(263 citation statements)
references
References 23 publications
12
246
1
4
Order By: Relevance
“…Despite studies on the formation of cartilage tissue from chondrocytes cells, 18,19 no report has been published on the production of cartilage tissue from adult human bone marrow-derived cells, including mesenchymal stem cells, by rotating three-dimensional dynamic culture. After 2 weeks of differentiation and induction of adult human bone marrow-derived cells to form cartilage, we compared the two culture methods using the RWV bioreactor and the pellet culture.…”
Section: Discussionmentioning
confidence: 99%
“…Despite studies on the formation of cartilage tissue from chondrocytes cells, 18,19 no report has been published on the production of cartilage tissue from adult human bone marrow-derived cells, including mesenchymal stem cells, by rotating three-dimensional dynamic culture. After 2 weeks of differentiation and induction of adult human bone marrow-derived cells to form cartilage, we compared the two culture methods using the RWV bioreactor and the pellet culture.…”
Section: Discussionmentioning
confidence: 99%
“…8 The construct's mechanical properties can be modulated by adjusting the parameters that define the culture environment, such as scaffold material, 25 hydrodynamic conditions, 36,59 mechanical loading, 5,37,39 addition of growthfactors, 37,44 cell seeding density and nutrition. 40 Although it has been shown that mechanical properties which approach those of natural cartilage can be obtained after long term culture, 17 there is still a lack of control over the functional development of tissue engineered constructs.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment of Freed (Freed, et al 1997) had reported the changes of the cartilage structure and the morphology of the chondrocytes under the real microgravity. Our result about the impairment of the microtubular system maybe is an earlier symptom of the cellular morphological change.…”
Section: Effect Of the Simulated Microgravity On The Activity Of Mitomentioning
confidence: 99%
“…In spaceflown rats with fractured fibula, formation of cartilage callus was minimal (Kaplansky,et al 199 1). Freed et al (Freed, et al 1997) studied the reconstructed cartilage under microgravity and found that the structure of this reconstructed cartilage as well as the morphology of the chondrocytes had changed. In our experiment, the cultured chicken embryonic chondrocytes were used as the experimental material.…”
Section: Introductionmentioning
confidence: 99%